2020
DOI: 10.1016/j.annonc.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Updated efficacy results from the JAVELIN Renal 101 trial: first-line avelumab plus axitinib versus sunitinib in patients with advanced renal cell carcinoma

Abstract: Background: The phase 3 JAVELIN Renal 101 trial ( NCT02684006 ) demonstrated significantly improved progression-free survival (PFS) with first-line avelumab plus axitinib versus sunitinib in advanced renal cell carcinoma (aRCC). We report updated efficacy data from the second interim analysis. Patients and methods: Treatment-naive patients with aRCC were randomized (1 : 1) to receive avelumab (10 mg/kg) intravenously every 2 weeks plus axitini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
312
0
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(334 citation statements)
references
References 14 publications
4
312
0
18
Order By: Relevance
“…In light of CheckMate214, JAVELINRenal 101 and Keynote-426 studies, no significant overall survival (OS) benefit was gained by any of the immune combinations for patients with a favorable risk profile (HR for OS: ipilimumab/nivolumab vs. sunitinib: 1.19 (95% CI 0.77-1.85), axitinib/pembrolizumab vs. sunitinib: 0.94 (95% CI 0.43-2.07), axitinib/avelumab vs. sunitinib: 0.812 (95% CI 0.336-1.960) (Motzer et al 2020;Keytruda-EMEA 2020;Choueiri et al 2020). A major limitation of these data are the short follow-up duration, which limits the data interpretation.…”
Section: How Should I Treat a Patient With Favorable Risk?mentioning
confidence: 99%
See 1 more Smart Citation
“…In light of CheckMate214, JAVELINRenal 101 and Keynote-426 studies, no significant overall survival (OS) benefit was gained by any of the immune combinations for patients with a favorable risk profile (HR for OS: ipilimumab/nivolumab vs. sunitinib: 1.19 (95% CI 0.77-1.85), axitinib/pembrolizumab vs. sunitinib: 0.94 (95% CI 0.43-2.07), axitinib/avelumab vs. sunitinib: 0.812 (95% CI 0.336-1.960) (Motzer et al 2020;Keytruda-EMEA 2020;Choueiri et al 2020). A major limitation of these data are the short follow-up duration, which limits the data interpretation.…”
Section: How Should I Treat a Patient With Favorable Risk?mentioning
confidence: 99%
“…In cases who exert favorable clinical parameters depicted Choueiri et al 2018Choueiri et al , 2020. To minimize the risk of immune-mediated adverse events, as well as high dose steroids application due to immune related adverse events, a careful patients based valuing is demanded to choose the best treatment regimen (Table 2).…”
Section: How Should I Treat a Patient At Intermediate Or Poor Risk?mentioning
confidence: 99%
“…17,18 Ongoing clinical trials and others recently concluded continue to study the efficacy of novel drug combinations, with special reference to the anti-PD-L1 agent avelumab or the anti-PD-1 antibody pembrolizumab with the VEGFR-inhibitor axitinib. 19,20 However, although a clinically relevant median response duration is reported, not all patients equally benefit from the currently available IO treatment, and the patient response rate is overall low. 17 Biological factors specific for certain individuals have a clear effect on this variation in response.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Immune checkpoint inhibitors, which already represent a standard treatment option in pretreated mRCC patients, are also revolutionizing the frontline treatment, since combination immunotherapy as well as combinations of immunotherapy with targeted agents have been shown to significantly improve the outcomes of treatment-naïve mRCC patients. [11][12][13][14][15][16] In RCC, immunotherapy influences adaptive immunity, allowing the immune system to recognize tumor antigens, maintain memory, and kill neoplastic cells. 17 Activation of adaptive immunity against foreign antigens is consequent to a complex chain of events, involving several receptors present on both neoplastic cells and immune cells, mediating inhibitory or activator signals.…”
Section: Introductionmentioning
confidence: 99%